Using technology to increase reach and optimize consent experience for a large-scale research program - Emma Coen; Daniel P. Judge; Samantha Norman; John T. Clark; Andrew Cates; Randolph Thornhill; Kelly Hunt; Lori McMahon; Leslie Lenert; Caitlin G. Allen (Journal of Clinical and Translational Science)
The consent process for research studies can be burdensome for potential participants due to complex information and lengthy consent forms. This pragmatic study aimed to improve the consent experience and evaluate its impact on participant decision making, study knowledge, and satisfaction with the In Our DNA SC program, a population-based genomic screening initiative. We compared two consent procedures: standard consent (SC) involving a PDF document and enhanced consent (EC) incorporating a pictograph and true or false questions. Decision-making control, study knowledge, satisfaction, and time to consent were assessed. We analyzed data for 109 individuals who completed the SC and 96 who completed the EC. Results indicated strong decision-making control and high levels of knowledge and satisfaction in both groups. While no significant differences were found between the two groups, the EC experience took longer for participants to complete. Future modifications include incorporating video modules and launching a Spanish version of the consent experience. Overall, this study contributes to the growing literature on consent improvements and highlights the need to assess salient components and explore participant preferences for receiving consent information.